Understanding the determinants of mobile banking continuance usage intention. Issue 6 (23rd August 2019) - Foroughi, Behzad; Iranmanesh, Mohammad; Hyun, Sunghyup Sean
Abstract : Purpose: The quality of people life and efficiency of banks can be improved by mobile banking (m-banking). The long-term success of m-banking depends on its constant use. The purpose of this paper is to investigate the determinants of m-banking continuance intention to use, using the technology continuance theory (TCT) by including the self-efficacy and channel preference. Design/methodology/approach: Empirical data from 369 Malaysian users who had prior experience with mobile banking were analysed, using partial least squares technique. Findings: The results confirmed that the TCT model had a high exploratory power in explaining users' perceived usefulness (PU), satisfaction, attitude and intentions to continue to use m-banking. Furthermore, self-efficacy and channel importance were important drivers of continuance intention in the context of m-banking. According to the results, perceived ease of use has no effect on PU and attitude in the post-adoption stage. Practical implications: The findings help bank managers to understand the importance of meeting customers' needs and expectations as a prerequisite in enhancing their satisfaction and favourable attitude towards m-banking and consequently their continuance intention. Originality/value: Based on the TCT model, this study contributes to the limited body of research on continuance intention to use m-banking. Furthermore, self-efficacy and channel preferences were added to the TCT model and the results confirmed the importance of enriching the TCT model to explain continuance intention to use information systems by adding contextual factors.